China rises - Farndon, John. ([S.l.] : Virgin Books, 2007)
With a population of 1.25 billion people and an economy that is the second largest in the world, China is a country we all need to take notice of. This entertaining, informative, up-to-date book is the ideal guide to this fascinating country's present - and its future. China is one of the world's oldest continuous civilizations and has produced some of the most significant human achievements of all time. With its current economic growth and increasing role in international affairs, it is fast becoming one of the most powerful and important countries in the world. But China refuses to conform to the expectations of the outside world. It is a communist state, but one in which business is booming. It is a nation that continues to support North Korea, even as it develops its relationships with the West. The Chinese government's controversial policies, from the one child policy to its history of repression of opposition groups and its policies towards Tibet and Taiwan, place it at odds with many of the world's most powerful nations. And yet as China's economy continues to grow, so will its influence and importance in the world. "China Rises" reveals the true nature of modern China and looks to the future to examine how China's growth will affect all of us. It will give readers a complete picture of this intriguing country - as it is now and as it will develop in the future.